The Role of ESPA in Japan’s Economic Security and Institutionalization of Economic Statecraft - Anindya Azzahra; Muhammad Aditya Purnomo (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2026)
This article analyzes the role of Japan’s Economic Security Promotion Act (ESPA) in strengthening the country’s economic security while simultaneously institutionalizing economic statecraft within the Indo-Pacific region. The enactment of ESPA in 2022 marked a significant shift in Japan’s strategic orientation from a post-war framework focused primarily on economic growth toward a more integrated approach that combines economic policy and national security objectives. Using a descriptive qualitative method, this article examines how ESPA functions through its four primary pillars: strengthening supply chain resilience, securing critical infrastructure, promoting strategic technologies, and protecting sensitive patents and innovations. The findings show that ESPA serves as a legal and political instrument that enables the Japanese government to reduce strategic dependence on external actors, particularly in critical sectors such as semiconductors, energy, and digital technologies. Furthermore, the study finds that ESPA institutionalizes economic statecraft by embedding economic security considerations into Japan’s regulatory and industrial policies.